Calculation of the elements of the complex dielectric tensor for anisotropic materials - Y.M. Aleksandrov; V.V. Yatsishen (Физика волновых процессов и радиотехнические системы, 2015)
The calculations of the real part of complex dielectric constant of silicene is produced by the first principles. Using the SIESTA program, the wave functions were constructed. For a sicilene layer the reflection frequency - angle spectra have been analyzed in the ATR configuration. The surface polaritons may be generated in this case.